From the Traditional Classroom to Mobile Microlearning: Analysing the Potential of Instagram for Chinese Language Learning - Rovira-Esteva a, Sara; Vargas-Urpí, Mireia (Sinología hispánica. China Studies Review, 2024)
In the context of the digital revolution taking place in education in general, social networks and the educational content they can offer are becoming increasingly important. Instagram is a paradigmatic example of m-learning (including mobile learning and microlearning). M-learning is characterised by short capsules in image or video, flexible and adapted to the social dynamics of consumption. In order to find out to what extent Instagram can play a relevant role in Chinese language learning and teaching today, this study has two main objectives. First, to analyse a sample of Instagram accounts for learning Chinese and, second, to assess the pros and cons of this medium from the perspective of teachers. To this end, we compiled a database of 100 Instagram accounts for learning Chinese and described them according to a detailed tagging system. The results show a bias towards contents that foster the practice of rather passive skills, the prevalence of image and video, resulting in less accessible materials, and the importance of formal aspects to easy the organization and retrieval of content. In conclusion, there is a great diversity of accounts, some of which stand out for their quality, although using them in classroom is certainly challenging.